Constructions of HIV Risk Among a Diverse Sample of HIV-Negative Young Men Who Have Sex With Men Who Are Repeat Testers. (15th April 2021) - Felner, Jennifer K.; Mittal, Maria L.; Hoenigl, Martin; Amico, K. Rivet; Grelotti, David J.; Eanes, Alex; Hess, Kristen; Crawford, Jessica; Smith, Laramie R.
Abstract : Introduction: To end the HIV epidemic, HIV prevention and pre-exposure prophylaxis (PrEP) promotion efforts must reach young men who have sex with men (YMSM) at greatest risk for HIV. This study qualitatively explored whether common metrics used by clinicians, scientists, and public health officials to objectively assess HIV risk align with how YMSM conceptualize their risk for HIV and the factors that shape YMSM's risk perceptions. Methods: Interviews with a racially/ethnically diverse sample of HIV-negative YMSM (ages 19–24 years, 60% Latinx; n = 20) examined conceptualizations of HIV risk within the context of repeat HIV testing. Iterative, applied thematic analysis examined how participants conceptualized and constructed their HIV risk, and compared participants' descriptions of their risk with a validated quantitative assessment of HIV risk that reliably predicts HIV seroconversion in this group. Results: Objective quantitative assessments of HIV risk poorly aligned with participants' perceived HIV risk. Participants described their current risk in relative terms (relative to past risk and relative to friends'/peers' risk) and described age/developmental stage and changes in knowledge about HIV prevention as key factors in risk changes over time. Other factors included substance use and trust/mistrust in sexual partners and scientific advances in HIV prevention (eg, U = U and PrEP). Factors that influenced participants' perceived HIV risk were similar regardless of objective risk assessment. Conclusions: Quantitative assessments of risk may poorly align with risk perception among YMSM. Although objective metrics can effectively target YMSM at greatest risk for HIV transmission, interventions to improve prevention behaviors and PrEP uptake may be more effective when tailored to bridge the disconnection between objective HIV risk assessments and YMSM's constructions of risk.